Comparison of methods for calculation of hydraulic characteristics of flow in non-pressure pipelines - A. L. Zuykov; N. T. Dzhumagulova; Abdulameer Layth Saeed Abdulameer (Vestnik MGSU)
Introduction. Three methods of calculation of hydraulic characteristics of flow in non-pressure pipelines are considered. These methods are experimental, traditional and using SewerCAD software. Currently, further development of hydraulic methods for calculating turbulent flows in non-pressure pipelines is possible due to new measurement methods and effective software products. To improve the accuracy of hydraulic calculations, it is necessary to conduct experimental studies. The purpose of the work is to determine the hydraulic characteristics of flow in non-pressure pipelines using three methods and find the relationship between them. When carrying out hydraulic calculations of pipelines that supply water over long distances, it is necessary to place increased demands on the accuracy of the results, as this is associated with monitoring emergencies. When fluid moves without pressure, the driving force that determines the flow velocity is the component of gravity directed along the flow. To this day, the formula that determines the average velocity of a uniform flow in a non-pressure pipeline, proposed by A. Chezy, is widely used. The work established the dependence of pipe filling on the average flow velocity at various slopes. A comparison was made of the average velocity obtained as a result of experimental studies and calculations using SewerCAD programme. The validity of the practical use of the proposed methodology is confirmed by the results of processing experimental data both by the authors and by other researchers.Materials and methods. Methods of calculation of turbulent flows in non-pressure pipelines using experimental data, traditional methods and computer technologies were applied, which increases the accuracy of the calculated flow parameters and the reliability of the pipeline system.Results. The results of the experiment, SewerCAD programme and traditional method of velocity calculation at different flow rates for non-pressure polyethylene pipes with a diameter of 100 mm with a pipeline filling from 0.1 to 0.8 are presented.Conclusions. Laboratory researches were carried out to determine the hydraulic characteristics of the flow of a polyethy-lene pipeline with a diameter of 100 mm. Corresponding dependencies for the average velocity between the experimental results and SewerCAD programme for a non-pressure system were obtained.